A genetic basis for multiple sclerosis severity: Red herring or real?. Issue 6 (December 2016) - Jokubaitis, Vilija G.; Butzkueven, Helmut
Abstract: Multiple Sclerosis (MS) is an autoimmune degenerative disease of the central nervous system, characterized by multifocal demyelination and neurodegeneration. The genetic architecture of MS is complex, where genetic risk has been attributed to over 100 polymorphic loci each with small odds ratios. MS is a highly heterogeneous disease with numerous clinical and paraclinical endophenotypes. To-date, no genetic variant has been associated with clinical outcome, however, evidence exists that MS outcomes, like risk, are to an extent also controlled by genetic variation. Here we summarise the current evidence for genetic determination of disease outcomes and make recommendations for future research directions. Highlights: No genetic variant has been found to be associated with disease outcomes to-date. Evidence of a genetic basis for MS outcome determination exists. Genetic variants are likely to be phenotype-specific.